Relationship between phorophyte variables and vascular epiphyte richness in the Pantanos de Centla, Tabasco, Mexico - Jiménez-López, Derio A.; Roblero-Velasco, René de Jesús; Martínez-Meléndez, Nayely; Ocampo, Gilberto; Gallardo-Cruz, José Alberto (Instituto de Ecología, A.C., 2017)
Background and Aims: Vascular epiphytes are rare elements of mangrove-dominated forests because sea salinity causes extreme conditions that difficult their establishment. In southern Mexico, most of the studies about the relationships between epiphytes and phorophytes have been carried out in montane forests, while the mangrove forests have received little attention. Our aim was to analyze the relationships between epiphytic species richness and the phorophyte characteristics of Rhizophora mangle, an endangered species under the NOM-059-SEMARNAT- 2010, in the “Pantanos de Centla” Biosphere Reserve located in the north-east of the state of Tabasco.Methods: The relation between species richness of epiphytes and several variables of the phorophytes, such as the aerial root coverage, diameter at breast height (DBH) and height, was evaluated using linear regression models. In addition, phorophytes were divided into five vertical zones to analyze the vertical distribution of the epiphytes using the Sørensen and Margalef indexes.Key results: Seventeen species of epiphytes were recorded. Orchidaceae and Bromeliaceae were the families with the highest species richness (six each). The most representative genus was Tillandsia (Bromeliaceae) with five species. The epiphytic species richness was significantly correlated with phorophyte aerial root coverage and DBH. The phorophyte zones I and III were the most similar because they shared 47% of all recorded species. The zone I (aerial roots) showed the highest epiphyte species richness. In the zone V (outer portion of the canopy) only Selenicereus testudo (Cactaceae) was registered, a species that was found in all five zones of the phorophyte. The mangrove area studied has a relatively high epiphyte richness in spite of the high salinity present in its flooded habitat.Conclusions: Epiphytic species richness was determined by the variation in size of the phorophytes. The aerial roots of R. mangle are an additional niche for the colonization of epiphytes and not just a supporting structure for the unstable soil of the mangrove ecosystem.